Art history or literature? Documenting Icelandic artists’ books - Árnadóttir, Arndís S. (Art Libraries Journal, 2000)
The project of creating a catalogue of Nordic collections holding artists’ books, initiated at ARLIS/Norden’s annual meeting in Helsinki in May 1996, was the starting point for a survey of the material held in Icelandic art libraries. This focused on the type and size of the collections of artists’ books in four art institutions covering twentieth century art in Iceland, and examined the current documentation standards applied to artists’ books in Icelandic collections and the extent of national bibliographic control.